Large-scale association analysis identifies 13 new susceptibility loci for coronary artery disease - Schunkert, Heribert; März, Winfried (Nature genetics, 2011)
Heribert Schunkert and colleagues report a meta-analysis of 14 genome-wide association studies of coronary disease (CAD) followed by replication in additional cohorts. They confirm 10 previously associated loci and identify 13 loci newly associated with CAD.
Gesehen am 28.10.2022